Kajian Tentang Konsep Dasar Dan Ruang Lingkup Manajemen Madrsah - Noorma Dewi Firnanda; Ade Nur Isnaini; Mardiyah Mardiyah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Management iis ia iprocess, ithen iorganization ias ia iframework, istructure ior icontainer ifor ipeople iwho iwork itogether. iThus, imanagement iis ia istep itowards iachieving igoals ithrough ithe ipotential iof iother ipeople iwho ibecome ia ivessel iin ithe iorganization. iTherefore, iit iis iclear ithat ithe irelationship ibetween imanagement iand ithe iorganization iis ilike itwo isides iof ia icoin. iThere iare ifour ifoundations ifor ideveloping imanagement iaccording ito ian iIslamic iview, inamely: i1) iTruth, i2) ihonesty, i3) iopenness, iand i4) iexpertise. iMadrasas ias iIslamic iEducation iInstitutions ihave iexperienced imany idynamics iin ithe icourse iof ihistory, itheir iexistence iis ia inecessity ifor ithe iMuslim icommunity. iHowever, iif imadrasas iare inot iprofessionally imanaged iwith isystematic imanagement, ithey iwill icertainly iface iserious iproblems iamidst ithe iaccumulation iof icompetition. iTherefore, ithe imanagement iof iManasi iIslamic ieducational iinstitutions iis inot ifresh. iIn ifact, ithe iprinciples iof ieducation iin iIslam inormatively ido inot iclash iwith ithe iconcept iof imanagement. iManagement ifunctions iinclude iplanning ifunctions, iorganizing ifunctions, imovement ifunctions, iand imonitoring ifunctions. iThe iimplementation iof ithese ifour ifunctions imust ibe icontinuous, iif ione iis inot iimplemented ithen ia imanagement iwill inot iachieve imaximum igoals/results. inon-human iresources ito iachieve imadrasa igoals ito ibe ieffective iand iefficient. iThe iscope iof ieducation imanagement iin imadrasas iincludes iall itypes iof imanagement iactivities ithat iare idirectly ior iindirectly iinvolved iin ieducational iactivities iin imadrasah imanagement, ithere iare ieight iareas iof imanagement imanagement icurriculum imanagement, istate iof ihuman iresources, ihuman iresource imanagement, ifacilities iand iinfrastructure imanagement, ifinancial imanagement i, ischool imanagement iand icommunity imanagement iand imanagement iof ispecial iservices. iAll iof ithese imanagement iareas ihave itheir irespective iroles iin ideveloping ithe iquality iof imadrasas. iSo ifrom iall iof ithese iareas iit iis inecessary ito ipay ispecial iattention iso ithat ithese ifields ican irun iaccording ito itheir iduties iand iroles ito iincrease ithe ieffectiveness iand iefficiency iof iwork iprograms. iSchools ias iformal ieducational iinstitutions icurrently ifocus itoo imuch ion iacademic iintelligence ifactors iand idon't ieven ilike iprocedural imatters ior ireliable iSpanish ibut iplace imore iemphasis ion ithe iachievement iof iparticipants iin iterms iof iintellectual iintelligence iwhich iultimately ileads ito ivarious iacademic imeasures. iCurrently, ithe iIndonesian igovernment iand isociety iare iin ia icrisis isituation iin ivarious ifields, iespecially ithe icrisis iin ithe ieducation isector ias ievidenced iby ithe ilow iquality iof ihuman iresources iand ithe ilow iquality iof itertiary iinstitutions.